Has COVID-19 affected the publication productivity of neurosurgeons in UK and Republic of Ireland? A bibliometric analysis [version 2; peer review: 1 approved, 2 approved with reservations, 1 not approved] - Jigi Moudgil-Joshi; Hariss G Paremes Sivam; Chandrasekaran Kaliaperumal (Health Open Research)
Background Our aim was to determine the impact of the COVID-19 pandemic on the publication productivity of neurosurgeons in the United Kingdom and Republic of Ireland. Methods Using bibliometric data we quantified and analysed the academic output of neurosurgeons in England, Scotland, Northern Ireland, Wales, and the Republic of Ireland, between two time periods i.e., January 2017 to December 2019 and January 2020 to March 2022, as a representative capture of the academic climate before and after the start of the COVID-19 pandemic. The consultant neurosurgeons were grouped according to their departments, title, sex, subspecialities and additional research qualifications. Using data charts on Scopus author directory, the total number of publications, citations and h-indices of each neurosurgeon were obtained over the two time periods. The median and mean of these 3 parameters were computed and the median values were analysed and tested for significance using a Mann Whitney-U test according to the groups. Results Our analysis conveyed a statistically significant increase (2440 publications and between January 2020 and March 2022 there were 2548 publications p<0.05) in the total number of publications after the start of the COVID-19 pandemic compared to before. There was a statistically significant decrease in the mean number of citations (mean 55.24 vs 57.01, p<0.05), after the start of the COVID-19 pandemic. This trend was observed in both sexes, in authors without an additional MD/PhD and in authors who sub-specialized in neuro-oncology. Overall, there was a significant decrease in H-index after the start of the pandemic compared to before (median h-index:1.00 and 2.00; mean h-index:1.8 and 3.4 respectively). Conclusions There appears to be an apparent increase in total number of publications after the start of the COVID-19 pandemic, most authors have registered a reduction in citations and h-indices, suggesting a lower impact and unequal distribution of the abovementioned increase.